The Impact of Ilness Acceptance on Quality of Life of Patients with Multiple Sclerosis — Preliminary Study - Joanna Rosińczuk; Katarzyna Rychła; Joanna Bronowicka; Aleksandra Kołtuniuk (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Multiple Sclerosis (MS) is a disease that often changes the life of a patient and his or her immediate family. The lack of aetiology, young age and the inability to control the dynamics of disease development and the lack of complete cure are factors impeding the acceptance of the disease. Aim. Evaluation of the effect of disease acceptance on quality of life (QOL) of MS patients. Material and Methods. The study was conducted among 128 people (93 women and 35 men) with MS using a shortened quality of life questionnaire of The World Health Organization (WHOQOL-BREF), as well as the Acceptance of Illness Scale (AIS) and the Author’s Own Survey (AOS). The research project was approved by the Bioethics Committee of Wrocław Medical University (no. KB-444/2016). The research material was subjected to statistical analysis using the Statistica program version 13.1. Results. Analysis of the research material revealed that only one in three respondents was satisfied or very satisfied with their health condition, the lowest respondents rated the quality of their lives in the somatic domain, every fourth respondent does not accept his or her own disease, the higher the level of disease acceptance, the higher the score obtained in the WHOQOL-BREF questionnaire. Conclusions. The level of disease acceptance significantly affects QOL patients with MS. (JNNN 2017;6(4):157–162)